Maternal education and equity in breastfeeding: trends and patterns in 81 low- and middle-income countries between 2000 and 2019 - Paulo A. R. Neves; Aluisio J. D. Barros; Giovanna Gatica-Domínguez; Juliana S. Vaz; Phillip Baker; Chessa K. Lutter (BMC, 2021)
Abstract Background In low- and middle-income countries (LMICs), low levels of formal maternal educational are positively associated with breastfeeding whereas the reverse is true among women with higher levels of formal education. As such, breastfeeding has helped to reduce health equity gaps between rich and poor children. Our paper examines trends in breastfeeding and formula consumption by maternal educational in LMICs over nearly two decades. Methods We used 319 nationally representative surveys from 81 countries. We used WHO definitions for breastfeeding indicators and categorized maternal education into three categories: none, primary, and secondary or higher. We grouped countries according to the World Bank income groups and UNICEF regions classifications. The trend analyses were performed through multilevel linear regression to obtain average absolute annual changes in percentage points. Results Significant increases in prevalence were observed for early initiation and exclusive breastfeeding across all education categories, but more prominently in women with no formal education for early breastfeeding and in higher level educated women for exclusive breastfeeding. Small decreases in prevalence were seen mostly for women with no formal education for continued breastfeeding at 1 and 2 years. Among formula indicators, only formula consumption between 6 and 23 months decreased significantly over the period for women with primary education. Analysis by world regions demonstrated that gains in early and exclusive breastfeeding were almost universally distributed among education categories, except in the Middle East and North Africa where they decreased throughout education categories. Continued breastfeeding at 1 and 2 years increased in South Asia, Latin America and the Caribbean, and Eastern Europe and Central Asia for primary or higher education categories. Declines occurred for the group of no formal education in South Asia and nearly all education categories in the Middle East and North Africa with a decline steeper for continued breastfeeding at 2 years. With a few exceptions, the use of formula is higher among children of women at the highest education level in all regions. Conclusions Over the course of our study, women with no formal education have worsening breastfeeding indicators compared to women with primary and secondary or higher education.